A new method to fabricate the cathode by cyclic voltammetric electrodeposition for electro-Fenton application. (20th July 2020) - Zhu, Weihuang; Li, Yaqi; Gao, Ying; Wang, Chen; Zhang, Jianfeng; Bai, Huiling; Huang, Tinglin
Abstract: To develop a stable and efficient cathode applied in electro-Fenton is indispensable. In current study, the carbon felt (CF) was modified by the cyclic voltammetric (CV) electrodeposited anthraquinone 2-sulfonate (AQS) and polypyrrole (PPy). The newly fabricated CF/AQS/PPy cathode by CV electrodeposition method was applied in electro-Fenton, which showed higher stability and efficiency compared with that of the traditional potentiostatic electrodeposited (TPED) method. The yield of the electro-generated H2 O2 and the degradation efficiencies of the target pollutant (RhB) in electro-Fenton with the newly fabricated cathode were around 10 times and 5 times higher than those of the unmodified CF cathode respectively. Recyclability evaluation showed that the degradation efficiency kept a good stability and could reach 100% within 1 h reaction time. The significantly enhanced performance and stability were attributed to the reduced charge transfer resistance (Rct) of the fabricated CF/AQS/PPy cathode decorated by the high conductive PPy and catalytic activity of AQS for oxygen reduction. The modification could result in an elevated extent of oxygen reduction to generate more O2 -, which subsequently combined with the protons to produce H2 O2, the indispensable reactant to form reactive OH in the Fenton's process. The quenching experiment and EPR determination further confirmed the existence of OH and O2 - free radicals in electro-Fenton equipped with the newly fabricated cathode. Graphical abstract: Image 1 Highlights: A CF/AQS/PPy cathode was newly fabricated by CV electrodeposition method. The 10-CV cathode has the highest electro-catalytic activity. The cathode fabricated by the new CV method showed a high stability and efficiency. The mechanism of the electro-Fenton with the prepared cathode was proposed.